2020
DOI: 10.1007/s13300-020-00932-9
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Gestational Diabetes and Pregnancy Outcomes

Abstract: Introduction: Pre-gestational, type 1 and type 2 diabetes are associated with adverse neonatal outcomes and increased rates of emergency caesarean sections. Methods: We studied pregnancy outcomes associated with pre-gestational diabetes in 174 women who attended the National Maternity Hospital in Dublin, Ireland, between 2015 and 2017. Results: Fifty women (28.6%) had type 2 diabetes mellitus, and 124 women (71.4%) had type 1 diabetes mellitus. Women with type 2 diabetes mellitus were older (36 vs. 34 years, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
2
9
0
1
Order By: Relevance
“…According to our data, women with HbA1c > 7% tend to deliver significantly earlier (35.57–38.00) than women with HbA1c ≤ 7% (38.00–38.43). Several factors could explain the higher rate of preterm birth in women with HbA1c, including the high trend of iatrogenic birth at 35–36 weeks in the presence of both an altered glycemic diary and ultrasound signs of metabolic failure, or the increased rate of hypertensive disorders and preeclampsia [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to our data, women with HbA1c > 7% tend to deliver significantly earlier (35.57–38.00) than women with HbA1c ≤ 7% (38.00–38.43). Several factors could explain the higher rate of preterm birth in women with HbA1c, including the high trend of iatrogenic birth at 35–36 weeks in the presence of both an altered glycemic diary and ultrasound signs of metabolic failure, or the increased rate of hypertensive disorders and preeclampsia [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, type 2 diabetes accounted for 30% of cases of pre-gestational diabetes and this figure now approaches 34% [14]. While this rate is close to that seen in other large obstetrics centres in Ireland, it differs from a 2014 study from the west of Ireland which found that type 2 diabetes made up 40% of all pre-gestational cases [22,11]. Our evaluation of smaller versus larger centres also found that there is a 4% difference between larger (mostly urban) and It is also noteworthy that more than 50% of women with type 1 diabetes have a BMI above 24.9 kg/m 2 which is reflective of increased obesity rates in diabetes.…”
Section: Cohort Characteristics and Pregnancy Preparednessmentioning
confidence: 57%
“…19,21,30,34,38,39,43,45,46,48,49 The remaining 28 studies compared perinatal outcomes according to each insulin administration modality among 5518 pregnant persons (3282 [59.5%] MDI vs 2,236 [40.5%] CSII) with pregestational DM and were quantitatively synthesized in the meta-analysis. 8,18,20,[22][23][24][25][26][27][28][29][31][32][33][35][36][37][40][41][42]47,[50][51][52][53][54][55] For the primary maternal outcome, CSII therapy was associated with greater odds of CD (20 studies: 63.24% vs 56.49%, OR 1.33 [95% CI 1.15-1.54]; Figure 2), with no significant heterogeneity between studies (I 2 = 0.0%, P = .58). We confirmed the robustness of this positive association LGA, birthweight…”
Section: Meta-analysis and Synthesis Of Resultsmentioning
confidence: 99%
“…Six prospective observational cohort studies (including two secondary analyses of randomized controlled trials evaluating CGM therapy) and 33 retrospective cohort studies published from 2010 to 2022 met inclusion criteria and were selected for the systematic review (Figure 1 and Table 1). 8,18-55 In aggregate, the 39 studies included in the systematic review included 7528 pregnancies.…”
Section: Resultsmentioning
confidence: 99%